New aspects of sustainable development as a factor of competitiveness in the EU - Brankica Todorovic (CES Working Papers, 2018)
The process of integration and future developments within the European Union (EU) covers the issues of environmental protection, sustainable development and energy efficiency. These issues are becoming a significant part of economic and social development and appear as a factor for assessing the competitiveness of the EU countries. Therefore, this paper focuses on: the implementation of achieving the climate and energy objectives in line with the Europe 2020 Strategy, the environmental sustainability of EU countries under the Environmental Performance Index (EPI) and the assessment of the competitiveness of the EU countries on the basis of ecological development.
Keywords: P28; O44; Q56; 330; sustainable development; environment; competitiveness